Pengaruh Pemberian Ebook Multimodality Interaktif melalui Metode Student Centered Learning (SCL) terhadap Minat Belajar Mahasiswa Keperawatan di Era Society 5.0 - Sapariah Anggraini; Rifda Nur Achriyana Arif; Muthmainnah Muthmainnah; Yuza Olsi Rahmi; Zikran Zikran (Poltekkes Kemenkes Padang, 2025)
Welcoming the era society 5.0, Nursing Education make adjustment by implementing a digital-based and focused learning process Student Centered Learning (SCL). However, the problem that exists is lecturers still play an important role as the main learning source (Teacher Centered Learning). Students tend to be passive because they only listen to explanations of material from lecturers. EBook multimodality interactive developed to help improve lecturers' abilities in the digital field and help increase student interest in learning. This research aims to analyzing the effect of providing interactive multimodality EBooks using the SCL method on nursing students' learning interest in this era society 5.0. The research design used quasi experimental with post-test control group design. The research was conducted in September-November at the Nursing Study Program at Universitas Lambung Mangkurat.The sample was 84 respondents with Total Sampling. Statistical test using independent sample t-test with a significance level of 0.05. Measuring student interest in learning using a questionnaire. Significance value p-value of 0.001 (<0.05) with a value of 95% confidence interval amounting to 3,513-6,261 so it can be concluded that there is an influence of giving EBook multimodality interactive through the SCL method on nursing students' learning interest in this era society 5.0. EBook multimodality interactive developed can be applied by lecturers in every nursing course, making it easier for students to carry out independent learning and interact digitally.